Sites of Asian interaction : ideas, networks and mobility - Harper, T. N.; Amrith, Sunil S. (Cambridge University Press, 2014)
"Develops the rich historical literature on port cities across Asia, the quintessential sites of Asian cosmopolitanism, as well as more recent work on the 'moving metropolises' and 'mobile cities' of contemporary Asia"--Provided by publisher.